Personal Innovativeness, Perceived Usefulness, Perceived Ease of Use, and Trust Asdeterminants of Mobile Payment Utilization - Jefferson; Efrata, Tommy Christian (Review of Management and Entrepreneurship, 2023)
Because of technological advances, the role of cash as a means of payment began to shift and was eventually replaced by digital payments. Quick Response Code Indonesian Standard is one of the digital payment methods developed in Indonesia (QRIS). The goal of this study is to determine what factors influence people’s intentions to use QRIS as a mobile payment in Indonesia, as measured by personal innovativeness, perceived usefulness, perceived ease of use, and trust. Non-probability sampling was used in this study. Researchers collected data from 241 respondents by distributing questionnaires online via Google Form. The measurement scale used in this study is a linear scale. SEM-PLS is used to process data. According to the findings of this study, perceived usefulness, perceived ease of use, and trust influence the intention of Indonesians to use QRIS, whereas personal innovativeness has no effect. As far as researchers are aware, there are still few studies that specifically discuss the phenomenon of increasing QRIS transaction volume in Indonesia in general, so this research is expected to contribute to the advancement of business and management science. The findings of this study suggest alternative strategies for mobile payment service providers in countries with similar characteristics.